Narratives of the Tribe of Hamadān on the Prophet Mohammed (peace be upon him) - Collection and Study - Sharib, Abdullah Rajeh (Journal of Islamic Sciences, 2023)
This study aimed to collect narrations pertaining to the arrival of the Yemeni Hamadān tribe delegation to Prophet Mohammed (Peace Be upon Him)، from a variety of sources، including the Sunnah، Alssīrh books، books of al-Mughāzī، and printed historical texts. Then، the researcher endeavors to extract the most salient religious concepts، lessons، and morals gleaned from the subject matter، in addition to tracking the relevant specialized scientific material. To that end، the researcher shall proceed to scrutinize the sources in order to discern the authenticity of the information، drawing upon the methodology of the critics in their evaluation of the narrations.The study's findings have identified a significant impact of three historical events، namely the Treaty of Al-Ḥudaybīyah، the Conquest of Makkah، and the Battle of Tabūk، on the movement of delegations during the time of the Islamic state. Specifically، the Treaty of Al-Ḥudaybīyah played a crucial role in breaking down the barrier that had been erected by the Quraysh between the Arab tribes and the Prophet Mohammed (Peace Be upon Him)، allowing for the freer movement of delegations. Similarly، the Conquest of Makkah shattered the hopes of those who had relied on the Qurayshin opposing the Islamic state، leading to an increase in the number of delegations that sought to ally themselves with the Prophet Mohammed (Peace Be upon Him). These milestones in the history of the Islamic state served to strengthen the position of the Prophet and facilitated the spread of Islam to new regions.
Keywords: Narratives; Delegation; Tribe; Hamadān; Investigation; Study